FlashRMSD: An Effective Approach for Symmetry-Corrected RMSD Calculation with Extensive Benchmark Analysis - Altunyan, Vahagn N. (Mathematical Problems of Computer Science, 2025)
Root-mean-square deviation (RMSD) is a crucial metric for quantifying molecular structure similarity. However, the associated combinatorial challenges complicate the calculation process when dealing with highly symmetric molecules. Although several open-source tools have been developed to perform symmetry-corrected RMSD computations, each has limitations in terms of speed, accuracy, or usability. In this paper, we introduce FlashRMSD, a novel, rapid approach for symmetry-corrected RMSD calculation. In addition, we present an extensive benchmark dataset to evaluate RMSD calculation tools and provide a comparative analysis of existing methods alongside our proposed tool.